Moose (Alces alces L.) browsing in young Scots pine stands in relation to the characteristics of their winter habitats. - Heikkilä, Risto; Härkönen, Sauli (Silva Fennica, 1993)
Moose ( L.) browsing was studied in young Scots pine ( L.) stands mixed with deciduous trees in high-density winter ranges. The proportional use of twig biomass decreased as the availability increased. The total as well as proportional biomass consumption were higher on the moist than on the dry type of forest. The per tree consumption of pine was higher on the moist type, where the availability of pine was lower. Deciduous trees were more consumed on the moist type, where their availability was relatively high. The consumption of pine saplings increased as the availability of birch increased. Pine stem breakages were most numerous when birch occurred as overgrowth above pine and at high birch densities. The availability of other deciduous tree species did not correlate with browsing intensity of Scots pine. Moose browsing had seriously inhibited the development of Scots pines in 6% of the stands, over 60% of available biomass having been removed. Rowan and aspen were commonly over-browsed and their height growth was inhibited, which occurred rarely by birch. There was no difference in the proportion of young stands in forest areas with high and low moose density. A high proportion of peatland forests was found to indicate relatively good feeding habitats in the high-density areas.Alces alcesPinus sylvestris